3D femtocell path loss model in wireless network - Zyoud, Alhareth M. T. (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Femtocells are home access points installed by end consumers inside their houses which are an important and a promising technology in future wireless networks. It was proposed as a solution to the indoor propagation problems and to increase the indoor bandwidth. However, many challenges need to be addressed before deployment of femtocells. One of the most important challenges are assessing and mitigating the interference. In order to calculate the Signal to Interference plus Noise Ratio (SINR), an accurate path loss model is required. Most of the studies in the open literature considered a two dimensional scenarios where the femtocell has specific location and uniformly distributed in the network. On the contrary, this research will consider more practical scenarios where the femtocell is randomly distributed in a three Dimensional (3-D) environment to accommodate interference from cells spaced horizontally on a terrestrial access or stacked vertically as in the case for office or residential towers. The vertical interference is still not considered in the open literature yet. The most important parameter that should be considered once calculating the interference is the path loss. Since femtocell is installed in an indoor environment, this thesis addresses only the indoor propagation channel. Most of the available propagation models are for long range communication networks like macro and micro cellular networks. Models for femtocell networks, where the effects of walls and floors are considered, appeared to be necessary. In this research six different models of indoor propagation were studied and compared with measured data. Comprehensive measurements were conducted in a four storey building using most popular frequencies for Long-Term Evolution (LTE) networks of 1.8 and 2.6 GHz. Three different scenarios with different numbers of penetrated walls and floors were considered. The results were analyzed statistically using linear and non-linear regression methods. Further, a three dimensional path loss model based on two distance concept is proposed for indoor femtocells. In this model, the path loss intercept is made equal to the free space losses. Two path loss exponents were proposed. The first one is the vertical exponent that equals 7.62, and was inferred based on the vertical propagation measurements. The second path loss exponent is the horizontal one (variable) and it is found to be a function of transmitter and receiver heights. This model is found to be suitable for applications in LTE wireless networks and maybe applied in both LTE and LTE-Advanced (LTE-A) system level simulators. In addition, path loss has been evaluated in terms of various antenna aspects such as polarization and directivity. Finally a three dimensional system level simulator is developed and integrated into the famous Vienna LTE simulator in order to help the researcher in LTE femtocell field to analyze and investigate more real scenarios of femtocell deployment. The developed simulator allows the researcher to locate a multi-storey building in the region of interest, choose the number of floors, determine the ceiling height, and allocate the position of the femtocell inside the house. The proposed three dimensional indoor propagation model is implemented in the simulator and is used to assess and model interference. Different parameters such as Signal to Interference plus Noise Ratio (SINR), and throughput, were studied especially for vertically stacked femtocells. Results indicate the validity of the proposed 3-D model and confirm that it is a more realistic tool for assessment and model of femtocell interference.